Fatigue and burnout in nurses during the COVID-19 pandemic - Pekince, Hatice; Aslan, Hakime (My University, 2022)
This research was conducted to assess the fatigue and burnout levels of nurses and the factors affecting those levels during the COVID-19 pandemic. This descriptive-correlational\rresearch was carried out with 270 nurses at a university hospital in the eastern region of Turkey. To collect data, ‘Information Form, ‘The Checklist Individual\rStrength’ and ‘The Maslach Burnout Inventory’ were used. It was found that the mean age of the nurses who participated in this study was 27.5±5.7 years, 73.3% were\rfemale, 82.6% were bachelor graduates, 63% were single, 35.2% worked in intensive care units. It was found that the nurses obtained a total score of 94.6±20.5 on the\rCIS and 48.4±8.3 points on the MBI. Nurses’ fatigue levels were high and burnout levels were moderate. A positive correlation was found between fatigue and burnout (r:\r.288**, p=.000). The difference between gender, weekly working hours, duration of professional experience (not with fatigue) and working unit and fatigue and burnout\rwas found to be statistically significant (p<0.05). It was found that various aspects of the COVID-19 pandemic have increased fatigue and burnout.
Keywords: Hemşirelik; Psikoloji